Synovial Chondromatosis in Woman with Symptoms Mimicking Early Stages Osteoarthritis: Case Report - Bagus Wibowo Soetojo; Faizal Arifianto Soehadak; Yunus Yunus (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACT  Synovial chondromatosis is a case that rarely found epidemiologically. It is a process which is benign in the synovial lining of joints, synovial sheaths, and bursae. It is the metaplastic process of synovium, which converts it into the cartilage and gets detached to become a loose body. Methods of this study are describing a case report of patient of Airlangga University Hospital that has synovial chondromatosis. A 38 years old woman, with a one-year history of pain, edema, and restriction of the left knee joint. Patient symptoms were insidious in onset, which gradually progressed. Decreased range of motion of her knee. The symptoms were mimicking of osteoarthritis. Considering the extensive involvement with multiple nodule masses inside the knee joint, we planned surgical management and open procedure. Total synovectomy was done, synovium and the masses were sent for histopathological examination which confirmed the diagnosis of synovial chondromatosis. In our case, the patient has clinical symptoms mimicking osteoarthritis of genu. Some study reported similar cases. Although synovium osteochondromatosis is a rare case and it should be kept as a differential diagnosis with chronic knee pain with swelling. Synovial chondromatosis is a rare case in the orthopedic patient. Diagnosis of synovial chondromatosis is often made following a thorough history, physical examination, and radiographic examination and histopathologic. In our case report, we present synovial chondromatosis in woman mimicking osteoarthritis.  Patient treated by surgical removal of the loose bodies followed by total synovectomy. Keywords: Synovial chondromatosis, osteoarthritis, total synovectomy